2020
DOI: 10.1007/s00426-020-01296-2
|View full text |Cite
|
Sign up to set email alerts
|

The prominent role of perceptual salience in object discrimination: overt discrimination of graspable side does not activate grasping affordances

Abstract: Responses to object stimuli are often faster when jutting handles are aligned with responding hands, than when they are not: handle-to-hand correspondence effects. According to a location coding account, locations of visually salient jutting parts determine the spatial coding of objects. This asymmetry then facilitates same-sided responses compared to responses on the opposite side. Alternatively, this effect has been attributed to grasping actions of the left or the right hand afforded by the handle orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Indeed, debriefing of subjects indicated that when deciding which side of the object would be used for grasping, subjects reported that they performed the task by identifying the location of the spout. The alignment effect reported by Pellicano and Binkofski (2020) was most likely produced by spatial attention being directed toward an object’s spout. Our stimuli included a teapot with a prominent spout as well as a handle.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…Indeed, debriefing of subjects indicated that when deciding which side of the object would be used for grasping, subjects reported that they performed the task by identifying the location of the spout. The alignment effect reported by Pellicano and Binkofski (2020) was most likely produced by spatial attention being directed toward an object’s spout. Our stimuli included a teapot with a prominent spout as well as a handle.…”
Section: Methodsmentioning
confidence: 91%
“…We now distinguish the above results from previous work suggesting that alignment effects obtained with a reach-and-grasp response do not reflect activation of motor representations, but instead are another form of spatial correspondence effect. Pellicano and Binkofski (2020) obtained no alignment effect on a reach-and-grasp response when the task-irrelevant object had no handle (asymmetry was established by the object’s spout). Two aspects of their procedure likely contributed to this outcome.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Futures researches should be specifically designed to study this temporal course and particular conditions inducing it especially considering that some studies were able to support the earlier and long-lasting nature of some potentiation effects (e.g. Pellicano, Koch, & Binkofski, 2017;Pellicano & Binkofski, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…painting a handle red). There is evidence for a bidirectional relationship between attention and affordance 30 , 31 , while other studies have shown that the correlation may not be particularly strong 32 34 . The relationship may be more nuanced and be affected by additional neurological systems, which would require additional study.…”
Section: Introductionmentioning
confidence: 92%